PENGARUH METALISITAS TERHADAP EVOLUSI BINTANG MASSIF - Hesyati Rosalinda Supyan, Nur
Stellar evolution describes the lives of the stars, from the stars were born to the end of their lives. Some parameters influences stellar evolution, one of them is metallicity. Astronomers use the word “metals” as a convenient short term for all elements heavier than hydrogen and helium. Stellar composition is often simply defined by the parameters X, Y, and Z, in which X is the mass fraction of hydrogen, Y is the mass fraction of helium, and Z is the mass fraction of all the remaining chemical elements. Thus, X+Y+Z=1. The abundance of metal elements (Z) presents in a star is called the metallicity of that star. By reviewing different metallicities, the stellar evolution described in H-R diagram will be different for each different metallicity and the chemical elements of the star will also be different. This can be seen in the early universe, the first stellar generations are different from solar metallicity stars due to their low metallicity and also they are thought to be very massive. Metallicity will affect to the rate of mass loss: mass loss becomes very weak at very low metallicity. Metallicity also will affect to the evolution in H-R diagram. At very low metallicity, the evolution track will be shorter after passing ZAMS (Zero Age Main Sequence) and stars are more compact and hotter compared with solar metallicity stars. In this final project, we study the effects of the metallicity to the evolution of massive stars through evolutionary modelling created using MESA (Modules for Experiments in Stellar Astrophysics). As the input, we use parameters such as initial mass, metallicity, rotation velocity, mixing parameter, and wind scheme, then the simulations are carried out to produce the physical parameters of the star, so that the output can be used to create the necessary diagrams for analyzing the stellar evolution.